Guidance for researchers wanting to link NHS data using non-consent approaches: a thematic analysis of feedback from the Health Research Authority Confidentiality Advisory Group: A thematic analysis of feedback from the Health Research Authority Confidentiality Advisory Group - Cross, Lauren; Carson, Lauren Emma; Jewell, Amelia; Heslin, Margaret; Osborn, David; Downs, Johnny; Stewart, Robert (International Journal of Population Data Science, 2020)
Introduction The use of linked data and non-consent methodologies is a rapidly growing area of health research due to the increasing detail, availability and scope of routinely collected electronic health records data. However, gaining the necessary legal and governance approvals to undertake data linkage is a complex process in England. Objectives We reflect on our own experience of establishing lawful basis for data linkage through Section 251 approval, with the intention to build a knowledgebase of practical advice for future applicants. Methods Thematic analysis was conducted on a corpus of Section 251 feedback reports from the NHS Health Research Authority Confidentiality Advisory Group. Results Four themes emerged from the feedback. These were: (a) Patient and Public Involvement, (b)~Establishing Rationale, (c) Data maintenance and contingency, and the need to gain (d) Further Permissions from external authorities prior to full approval. Conclusions Securing Section 251 approval poses ethical, practical and governance challenges. However, through a comprehensive, planned approach Section 251 approval is possible, enabling researchers to unlock the potential of linked data for the purposes of health research.